2003
DOI: 10.1002/sim.1597
|View full text |Cite
|
Sign up to set email alerts
|

Regression models for relative survival

Abstract: Four approaches to estimating a regression model for relative survival using the method of maximum likelihood are described and compared. The underlying model is an additive hazards model where the total hazard is written as the sum of the known baseline hazard and the excess hazard associated with a diagnosis of cancer. The excess hazards are assumed to be constant within pre-specified bands of follow-up. The likelihood can be maximized directly or in the framework of generalized linear models. Minor differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
660
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 703 publications
(664 citation statements)
references
References 18 publications
4
660
0
Order By: Relevance
“…Using the relative survival approach, we found that women with STEMI and NSTEMI had higher excess mortality rates compared with their male counterparts. Unlike standard survival, relative survival accounts for differences in background mortality across groups, allowing for the distinction between death due to the index AMI and deaths due to other causes, and avoids the risk of classification errors in cause‐of‐death records 27. Our results and the findings of a recent study by Baart et al13 illustrate that measuring relative survival and excess mortality may have important implications for acute coronary care.…”
Section: Discussionmentioning
confidence: 68%
“…Using the relative survival approach, we found that women with STEMI and NSTEMI had higher excess mortality rates compared with their male counterparts. Unlike standard survival, relative survival accounts for differences in background mortality across groups, allowing for the distinction between death due to the index AMI and deaths due to other causes, and avoids the risk of classification errors in cause‐of‐death records 27. Our results and the findings of a recent study by Baart et al13 illustrate that measuring relative survival and excess mortality may have important implications for acute coronary care.…”
Section: Discussionmentioning
confidence: 68%
“…This model, which was presented by Dickman et al in 2004, allows the calculation of excess hazard ratios through maximum likelihood estimation methods. 21 Different age categorizations were explored, and the regression models fit best when patients ages birth to 1 year and patients who did not receive radiation or surgery were excluded from the regression modeling.…”
Section: Methodsmentioning
confidence: 99%
“…Differences in 5-year relative survival by tumour morphology and hormone receptor status were modelled with a recently developed multiple regression approach based on generalised linear models and adopting the Poisson assumption for the observed number of deaths (Dickman et al, 2004). The relative excess risks (RERs) derived from these models quantify the extent to which the hazard of death in a given group differs from that in the reference category, after taking into account the background risk of death in the general population of each country or region.…”
Section: Methodsmentioning
confidence: 99%